How to Optimize Treatment With Ustekinumab in Inflammatory Bowel Disease: Lessons Learned From Clinical Trials and Real-World Data - Gutiérrez, Ana; Rodríguez-Lago, Iago (Frontiers in Medicine, 2021)
Ustekinumab is a fully human IgG1 monoclonal antibody that has been approved for the treatment of moderate to severe Crohn’s disease, and more recently moderate to severe ulcerative colitis. It binds with high affinity to the p40 subunit of human interleukin-12 and 23. This mechanism of action prevents the bioactivity of both interleukins, thus precluding their interaction with the cell surface receptor protein. The pivotal clinical trials (UNITI-1, UNITI-2 and IM-UNITI) demonstrated its clinical efficacy and safety, in naïve patients and also in those previously exposed to immunosuppressants and/or biologics. There is now an extensive experience with its use worldwide, corroborating its favorable profile even in patients with refractory disease. However, the number of medical treatment options available in inflammatory bowel disease are still limited. Hence, we should prioritize the treatments that have a greater probability of response in an individual patient. Our aim was to review and summarize all the available literature regarding the potential predictors of response to ustekinumab that can increase the success rate with this therapy in clinical practice.